THE EFFECT OF THE USE OF AI TECHNOLOGY (GPT Chat, Perplexity, Photomath, Canva), UNDERSTANDING OF SCIENCE CONCEPTS AND CRITICAL THINKING SKILLS IN SCIENCE LEARNING ON STUDENT LEARNING OUTCOMES IN PHASE D - Rifqi Aulia Mafaza; Ainun Rahmatun Nisak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the use of artificial intelligence (AI) technologies such as ChatGPT, Perplexity, Photomath, and Canva on the understanding of science concepts, critical thinking skills, and learning outcomes of Phase D students in science learning. Rapid technological developments offer significant opportunities to integrate AI into education to create a more interactive, efficient, and adaptive learning environment tailored to students' needs. However, empirical studies examining the effectiveness of AI technology in science learning, particularly for Phase D students, are still limited. This study used a quantitative method with a descriptive correlational approach. The subjects were Phase D students involved in technology-based science learning. Data were collected through questionnaires, learning achievement tests, and interviews to obtain comprehensive information regarding the use of AI technology. Instrument validity and reliability tests were conducted to ensure data quality. Data analysis was conducted using descriptive and inferential statistical tests to examine the relationship between the use of AI technology and the variables studied. The results showed that the use of AI technology had a positive and significant effect on students' understanding of science concepts. Students who utilized ChatGPT, Perplexity, Photomath, and Canva demonstrated a better understanding of science concepts compared to students who only used conventional learning methods. Furthermore, the integration of AI technology also improved students' critical thinking skills, as reflected in their ability to analyze, evaluate, and solve problems logically and creatively. Overall, student learning outcomes showed significant improvement, confirming that the integration of AI technology positively contributes to the quality of science learning.